2003
DOI: 10.1037/0022-3514.84.2.377
|View full text |Cite
|
Sign up to set email alerts
|

Counting blessings versus burdens: An experimental investigation of gratitude and subjective well-being in daily life.

Abstract: The effect of a grateful outlook on psychological and physical well-being was examined. In Studies 1 and 2, participants were randomly assigned to 1 of 3 experimental conditions (hassles, gratitude listing, and either neutral life events or social comparison); they then kept weekly (Study 1) or daily (Study 2) records of their moods, coping behaviors, health behaviors, physical symptoms, and overall life appraisals. In a 3rd study, persons with neuromuscular disease were randomly assigned to either the gratitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

91
1,874
2
133

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,406 publications
(2,176 citation statements)
references
References 52 publications
91
1,874
2
133
Order By: Relevance
“…They found that several of these interventions led to changes in happiness that persisted for at least six months. Finally, Emmons and McCullough (2003) found that interventions to increase thoughts of gratitude increased levels of positive affect. Although these experimental intervention studies are in the initial stages, they indicate that levels of happiness can be raised.…”
Section: Implications Of the Revised Modelmentioning
confidence: 98%
“…They found that several of these interventions led to changes in happiness that persisted for at least six months. Finally, Emmons and McCullough (2003) found that interventions to increase thoughts of gratitude increased levels of positive affect. Although these experimental intervention studies are in the initial stages, they indicate that levels of happiness can be raised.…”
Section: Implications Of the Revised Modelmentioning
confidence: 98%
“…When we decide to focus on all that is working in our lives without denying current burdens, we cultivate morepositive thinking and thankfulness. This practice lowers the threshold for feeling-good circuits to discharge in our brain and raises our baseline happiness index [6].…”
Section: Practice Gratitudementioning
confidence: 99%
“…W hen we decide to focus on all that is good in our lives, happiness increases, blood pressure drops, and heart rate decreases [6,7]. Unfortunately, in orthopaedic surgery, it can be challenging to stop and take note of all of the good stuff.…”
mentioning
confidence: 99%
“…That being said, it is apparent how gratefulness accounts for the attainment of positive emotions like happiness. To support this claim, Emmons and McCullough (2003) demarcated on individuals' inclination to count blessings as a way to enhance gratitude that is predictive of subjective well-being.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A good number of studies identified several predictors of gratitude which includes self-esteem (Bernstein & Simons, 1974), positive affect (Emmons & McCullough, 2003;Froh, Kashdan, Ozimkowski, & Miller, 2009;Froh, Sefick, & Emmons, 2008;Froh, Yurkewicz, & Kashdan, 2009), and life satisfaction (Froh, Yurkewicz, & Kashdan, 2009;Park, Peterson, & Seligman, 2004;Peterson, Ruch, Beermann, Park, & Seligman, 2007;Wood, Joseph, & Maltby, 2009). From such findings, it can be assumed that gratitude is not just a mere interpersonally-derived construct but a character that may be intrinsically-motivated.…”
Section: Conceptual Frameworkmentioning
confidence: 99%